Rhetorical Structure in Scientific Article Introduction Section Written by Tertiary Students - Zein, T. Thyrhaya; Sinar, T. Silvana; Nurlela, Nurlela; Syahputra, Fikry Prastya (Soegijapranata Catholic University, 2023)
This pilot research objective is to investigate the rhetorical structure of an introduction section of scientific articles written by tertiary students of social and humanity studies. The research method used is qualitative, which applied purposive sampling in collecting the data. Four journals from Talenta Publisher were selected based on several characteristics, such as socials and humanities discipline, English articles written by undergraduate and post-graduate students, and published in the last two years (2019-2020). The data analysis used an interactive model by applying data collection, condensation, display, and conclusion drawing and verification. The Creating Research Space (CaRS) model used for data analysis is to describe the rhetorical structure of the introduction section in the articles. The results of this research stated that Move 1 Step 2 (making topic generalizations), with a percentage of 31%, is identified as the dominant rhetorical structure. On the other hand, move 2 Step 1c (question-raising) and Move 3 Step 3 (indicating article structure) are not realized in all data. In conclusion, the majority of authors do not follow the standard rhetorical structures of a scientific article. Some of these journals have not applied rhetorical structure, which is an important thing that must be followed, such as Move and Steps, which consists of components: background of the study, research gap, problem statement, and research aim